Lustmord: sexual murder in Weimar Germany - Tatar, Maria (Princeton University Press, 2021)
Frontmatter -- Contents -- LIST OF ILLUSTRATIONS -- ACKNOWLEDGMENTS -- PART ONE Sexual Murder: Weimar Germany and Its Cultural Legacy -- Chapter One. Morbid Curiosity: Why Lustmord -- Chapter Two. "Ask Mother": The Construction of Sexual Murder -- Chapter Three. Crime, Contagion, and Containment: Sexual Murder in the Weimar Republic -- PART TWO Case Studies -- Chapter Four. Fighting for Life: Figurations of War, Women, and the City in the Work of Otto Dix -- Chapter Five. Life in the Combat Zone: Military and Sexual Anxieties in the Work of George Grosz -- Chapter Six. The Corpse Vanishes: Gender, Violence, and Agency in Alfred Doblin's Berlin Alexanderplatz -- Chapter Seven. The Killer as Victim: Fritz Lang's M -- Chapter Eight. Reinventions: Murder in the Name of Art -- NOTES -- INDEX